Green Retrofitting of Cultural Heritage Building: A Case Study of Banten Grand Mosque - Venia Setyarandini; Agung Bayu Saputro (Department of Architecture, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2025)
The Banten Grand Mosque, as one of Indonesia’s oldest cultural heritage buildings, is more than just a place of worship; it embodies layers of history, identity, and spiritual significance for the local community. However, in the face of climate change and rising expectations for user comfort, the mosque is challenged to maintain a balance between thermal performance and architectural authenticity. This study aims to explore passive-based green retrofitting strategies that are both environmentally responsive and sensitive to conservation principles. Research was conducted through field observations, documentation, stakeholder interviews, and a review of relevant literature on green building and heritage conservation. The results highlight several thermal comfort problems, including limited cross ventilation, inadequate roof insulation, and high indoor humidity due to the hot-humid tropical climate. These conditions often cause discomfort for worshippers, particularly during peak hours of use. To address these challenges, the study proposes adaptive yet reversible interventions, such as optimizing natural ventilation through additional lattice panels, applying eco-friendly reflective paints, using natural insulation materials like coconut fiber, and introducing vegetation to enhance microclimate quality. These strategies emphasize the principle of non-invasiveness, ensuring that any modification can be removed without damaging the original structure. Through this approach, the Banten Grand Mosque has the potential to remain a living heritage site: conserving its historical and architectural identity while adapting to contemporary needs of energy efficiency and user comfort. The findings not only provide recommendations for this mosque but also contribute to the discourse on sustainable conservation of tropical heritage buildings.